An Overview of Macro-Economic Determinants of Real Estate Price in Nigeria - Abubakar Alkali, Musa; Sipan, Ibrahim; Najib Razali, Muhammad (International Journal of Engineering and Technology, 2018)
UnderstandingÂ the relationship between real estate price and macroeconomicÂ variables in developed countries is appreciated first by considering the housing role in the macro economy. In modern capitalist economy, real estate sector remains the most important element of aggregate demand. Since residential real estate comprises the bulk of countryâ€™s tangible capital, the study on relationship between residential real estate price and macro economic variables are very significant for formulation of social and economic policies. The aim of this studyÂ is to examines the relationship between real estate residential price and macroeconomic variables in Nigerian economy. The study identified GDP, inflation rate, exchange rate, interest rate and crude oil price as the major determinants of real estate price in Nigeria and they have significant impact on real estate market in general.Â Â